2022
DOI: 10.1111/dth.15817
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant nivolumab therapy may not improve disease‐free survival in resected acral lentiginous melanoma patients: A retrospective case series

Abstract: Adjuvant nivolumab therapy has been reported to improve the survival of melanoma patients. Acral lentiginous melanoma (ALM) has been reported to be less likely to respond to immune checkpoint inhibitors (ICIs) than other subtypes. However, the efficacy of adjuvant nivolumab therapy for ALM patients remains uncertain due to the low number of cases. In this single-center retrospective case series, we analyzed the clinical data of patients with resected stage III/IV ALM who were referred to our department between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…evaluated 27 patients with ALM treated in the adjuvant setting; 5 patients were treated with nivolumab and 22 patients were treated with either chemotherapy (n = 4), interferon beta (n = 12), or observation (n = 6). This study found no difference in disease-free survival between the groups, although the small sample size limits any clinically significant conclusions ( 41 ).…”
Section: Managementmentioning
confidence: 64%
“…evaluated 27 patients with ALM treated in the adjuvant setting; 5 patients were treated with nivolumab and 22 patients were treated with either chemotherapy (n = 4), interferon beta (n = 12), or observation (n = 6). This study found no difference in disease-free survival between the groups, although the small sample size limits any clinically significant conclusions ( 41 ).…”
Section: Managementmentioning
confidence: 64%
“…The acral type was an independent worse prognostic factor on multivariate analysis ( p = 0.015) [ 84 ]. A single-center retrospective study in Japan investigated adjuvant nivolumab ( n = 5) and other treatments ( n = 22; 12 patients with interferon β, 4 with chemotherapy, 6 with no treatment) and did not find a superior disease-free survival in the adjuvant nivolumab group over the non-nivolumab group [ 85 ]. These results suggest that the adjuvant anti-PD-1 inhibitor monotherapy exert an anti-tumor effect for acral melanoma, but may be less effective than for other types of cutaneous melanoma.…”
Section: Treatmentmentioning
confidence: 99%